PERANCANGAN APLIKASI E-MUSIC BERBASIS ANDROID - Daeli, Fonirius; Sitohang, Sunarsan (Computer Science and Industrial Engineering, 2021)
Abstract Music is one of the important things in people’s life, music is known as a combination of elements of tone, melody, song rhythm and other arrangements that combine in the form of sound. Music is very much in demand by people, especially Batam City, both in concerts, party events and even on personal gadgets. For this reason, renting a musical instrument is very difficult, because it is difficult for prospective tenants to get detailed information on renting musical instrument. Due to the lack of information, researchers provide a solution in the form of a musical instrument rental information application system which includes price information, detailed packages and online payments using the existing payment methods in the application. In conducting research, researchers used the rapid application development (RAD) method which was designed using UML tools consisting of use case diagram, activity diagram, sequence diagram and class diagram. The results of this study are in the form of an android application that is accessed on a personal smartphone or gadget. With the help of this application, it is hoped that the rental of existing musical instruments will be easier, especially in the city of Batam. Keywords: Andoid; Application; E-Music; Music; Musical Instrument Rental.